2016
DOI: 10.1149/2.0581610jes
|View full text |Cite
|
Sign up to set email alerts
|

A Gold Micro-Reference Electrode for Impedance and Potential Measurements in Lithium Ion Batteries

Abstract: Impedance measurements of lithium-ion batteries are a powerful tool to investigate the electrolyte/electrode interface. To separate the contributions of anode and cathode to the full-cell impedance, a reference electrode is required. However, if the reference electrode is placed inappropriately, the impedance response can easily be biased and lead to erroneous conclusions. In this study, we present a novel micro-reference electrode for Swagelok-type T-cells which is suitable for long-term impedance and referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
228
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 140 publications
(243 citation statements)
references
References 54 publications
(122 reference statements)
13
228
2
Order By: Relevance
“…Interfacial resistance of graphite anodes after formation at 25 • C in graphite/LNMO cells (this study) compared to graphite anodes in graphite/LFP cells from our earlier study. 13 The VC concentration is recalculated in units of mg VC /m 2 Graphite to assess for the slightly different areal loadings (namely ∼2.6 mAh/cm 2 geo in the graphite/LNMO cells and ∼2.2 mAh/cm 2 geo in the graphite/LFP cells, based on 340 mAh/g graphite ). The error bars represent the standard deviation between two measurements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interfacial resistance of graphite anodes after formation at 25 • C in graphite/LNMO cells (this study) compared to graphite anodes in graphite/LFP cells from our earlier study. 13 The VC concentration is recalculated in units of mg VC /m 2 Graphite to assess for the slightly different areal loadings (namely ∼2.6 mAh/cm 2 geo in the graphite/LNMO cells and ∼2.2 mAh/cm 2 geo in the graphite/LFP cells, based on 340 mAh/g graphite ). The error bars represent the standard deviation between two measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The investigated electrolytes consisted only of EC or VC with 1 M LiPF 6 (all from BASF SE, Germany). To distinguish between electrolyte oxidation and carbon corrosion, we used isotopically labelled 13 C-carbon electrodes coated on a polyester separator as working electrodes (see above). The oxidative stability of the electrolytes was investigated by a linear potential sweep from OCV (∼3 V vs. Li/Li + ) to 5.5 V vs. Li/Li + at a scan rate of 0.1 mV/s.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is largely related to the fact that in commercialscale cells, the ratio of active materials to electrolyte solution and void volume is typically ∼10 times higher compared to the lab-scale cells used here. 37,56 Strehle et al 16 recently showed that under these conditions, the majority of CO 2 released from VC reduction would remain dissolved in the electrolyte solution instead of being released into the gas headspace of the cell. This is illustrated by first estimating the amount of dissolved CO 2 by Henry's law 2: where n CO2(el) is the amount of CO 2 dissolved in the liquid electrolyte solution, V el is the volume of the electrolyte solution, c el is the total molar concentration of the electrolyte solution (i.e., solvent and salt) and K H is the Henry constant of CO 2 in the electrolyte solution in units of pressure.…”
Section: Discussionmentioning
confidence: 99%